1990
DOI: 10.1002/aic.690360802
|View full text |Cite
|
Sign up to set email alerts
|

The Benzylphenylether thermolysis mechanism: Insights from phase behavior

Abstract: The thermolysis of benzylphenylether (BPE) was examined at 320°C in liquid, vapor, and supercritical methanol phases as a probe of the reaction mechanism. Toluene and phenol were the major products in all cases, but observed selectivities were dependent upon the reaction phase. Isotopic labeling experiments demonstrated that methanol participated in the reaction network as a hydrogen donor through a free-radical mechanism. These results are consistent with free-radical steps for neat BPE primary pyrolysis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…This result is distinctly different from that of Wu et al 29), who reported that selectivities of phenol and toluene were almost the same (0.5).…”
Section: Reaction In Sc Methanolcontrasting
confidence: 99%
“…This result is distinctly different from that of Wu et al 29), who reported that selectivities of phenol and toluene were almost the same (0.5).…”
Section: Reaction In Sc Methanolcontrasting
confidence: 99%
“…The first studies on lignin model compound pyrolysis were reported by Klein et al (Klein & Virk, 1983;Simmons & Klein, 1985;Wu FIGURE 21 Thermal decomposition of xylose unit via a combination of free-radical and concerted pathways yielding furfural and glycoldehyde, glyoxal, acetone, and furfural (Adapted from Shen et al, 2010. Copyright 2010 Benjamin, Klein Michael, & Sandler Stanley, 2004). Phenethyl phenyl ether (PPE) represents the β-O-4 linkage present in native lignin.…”
Section: Ligninmentioning
confidence: 99%
“…Conversion of non-phenolic β-1 type model compound ( 7) into its α-methyl ether is a dominant reaction path due to the acidic character of the supercritical methanol. 16 Acid-labile hydroxyl groups such as α-hydroxyl group in the compound ( 7) can be eliminated to form quinonemethide-type intermediate under such an acidic condition, which is easily converted into α-methyl ether, and then further converted into tetramethoxystilbene (13), which is stable in supercritical methanol.…”
Section: β-1 Type Model Compoundmentioning
confidence: 99%